Assessing how Social Media Marketing Motivates Consumers to Purchase New Artists’ Offerings in the Music Industry - Oozeer, Aneesah (2018)
This exploratory study illustrates how social media marketing motivates music consumers to listen to new, smaller, lesser-known and independent artists. It uncovers the fact that music consumers are only driven to listen to the offerings of these artists but not induced to purchase the music. It is concluded in this case that social media acts as a double-edged weapon. Social media platforms allow music consumers to access music at their own convenience. Recommendations on these platforms are significantly important for these artists. Platforms use algorithm mechanisms to generate recommendations while individuals use the power that social media give to them to influence others in terms of music consumption. Electronic word-of-mouth prompts others to listen to new artists. Artists also have a platform on which they can share the contents of their offerings and this can help attract and maintain a following. However, there is an array of content that artists can post and the appeal works differently in each case. It mostly depends on the audience of the artists. Similarly, the frequency at which the artists post information depends on their audience. Yet the same promotional platforms are detrimental. Social media and music sharing platforms impede the purchase of music. Some explanations and recommendations are offered in the final chapter. Based on basic assumptions formed from the literature review and using qualitative research methods, this study explores the world of social media marketing in the music industry in the case of new, smaller, lesser-known and independent artists from the consumers’ perspective.